Exploration of conservation and development strategies with a limited stakeholder approach for local cattle breeds. (26th June 2019) - Schäler, J.; Addo, S.; Thaller, G.; Hinrichs, D.
Abstract : Many local breeds have become endangered due to their substitution by high-yielding breeds. To conserve local breeds, effective development strategies need to be investigated. The aim of this study was to explore conservation and development strategies based on quantified strengths, weaknesses, opportunities and threats (SWOT ) for two local cattle breeds from Northern Germany, namely the German Angler (GA ) and Red Dual-Purpose cattle (RDP ). The data comprised 158 questionnaires regarding both breeds' SWOT, which were answered by 78 farmers of GA and 80 farmers of RDP. First, data were analysed using the SWOT-Analytic Hierarchy Process (AHP ) method, which combines the qualitative strategic decision tool of SWOT analysis and the quantitative tool of AHP. Second, prioritised SWOT factors were discussed with stakeholders in order to form final conservation and development strategies at breed level. For GA prioritised strengths were daily gain, meat quality, milk production and the usage of new biotechnologies, weaknesses were genetic gain in milk production and inbreeding, opportunities were organic farming and breed-specific characteristics and threats were milk prices and dependency regarding the dairy business. Consequently, three conservation and development strategies were formed: (1) changing relative weights and the relevant breeding goal to drift from milk to meat, (2) increasing genetic gain and control the rate of inbreeding by the implementation of specific selection programs and (3) selection of unique and breed characteristic components on product level, that is, milk-fat and fine muscle fibers. For RDP defined strengths were robustness, high adaptability for different housing systems and a balanced dual-purpose of milk and meat, weaknesses were inbreeding, breed extinction, genomic selection with young bulls and milk yield, opportunities were organic farming and dual-purpose aspects and threats were milk and decreasing beef cattle prices. Thus, three conservation and development strategies were identified: (1) adjust relative weights and the relevant breeding goal to balance milk and meat yield, (2) increasing genetic gain and avoid extinction by implementing targeted selection programs and (3) selection of unique and breed characteristic traits on breed level, that is, environmental robustness. Quantified SWOT establish a basis for the exploration of conservation and development strategies at breed level. Explored strategies are promising even if the stakeholder approach was limited for small populations regarding a small number of stakeholder groups. The used approach reflects farmers' individual convenience better than existing quantitative strategy decision tools on their own.